Effect Of Snake Ladder Media Health Education On Behavioral Improvement In PHBS In Elementary School Students - Shofiatuz Zahro; Sri Utami; Rini Ambarwati; Miadi (International Journal of Advanced Health Science and Technology, 2025)
Clean and Healthy Living Behavior (PHBS) is an important indicator in the achievement of health as stated in the Sustainable Development Goals (SDGs) 2015-2030 program. However, the implementation of the PHBS program in the community is still not optimal. One effective educational method is to use snake and ladder media. This study aims to analyze the influence of snake and ladder media on improving PHBS behavior in elementary school children. This study uses a quasi-experimental design with a one group pre-test post-test with control group design. Sampling using the Simple Random Sampling Technique, the sample consisted of 52 students in grades 3-6. The independent variable is health education using snake and ladder media, while the dependent variable includes knowledge, attitudes, and actions. The research instruments include snake and ladder boards, questionnaires, and observation sheets. Data analysis used the Wilcoxon test and the Mann-Whitney test with a value of α<0.05. The results of the study showed an increase in knowledge, attitudes, and actions in PHBS, with a p-value of <0.001 (α<0.05) each, meaning that there was an influence of snake and ladder media health education on knowledge, attitudes, and actions in PHBS. In addition, there were differences in knowledge, attitudes, and actions between the intervention and control groups with a p<0.001 value. This shows that education using snake and ladder media is effective in improving PHBS behavior in elementary school children